STABILITY INDICATING HPLC METHOD FOR QUANTIFICATION OF RISPERIDONE IN TABLETS - Sigrid Mennickent; Marta de Diego; Bernd Liser; Lina Trujillo (Journal of the Chilean Chemical Society, 2018)
A stability- indicating LC method was developed and validated for the determination of risperidone in tablets.Quantitation was achieved by LC/DAD at 294 nm over the concentration range of 25.00 μg/mL to 250.00 μg/mL. Mobile phase was a mixture of water: glacial acetic acid 0.50 %: triethylamine 0.80 %: acetonitrile (65.00: 0.32: 0.52: 34.16, v/v), using a Purosphere STAR RP-18e 250 x 4.5 mm (5μ) column, and paroxetine as internal standard.The method exhibited an adequate linearity (r = 0.999), selectivity, precision (RSD ≤ 0.847 %) and accuracy (recoveries from 99.55 % to 101.35 %).Risperidone was subjected to the stress conditions of oxidative, acid, base, thermal and photolytic degradation. Risperidone was found no degrade in basic or acid stress conditions, neither in thermal stress exposition (50, 70 and 100 ºC) no at visible or UV stress conditions, during the time of the study. Only two degradation products were observed with peroxide oxidation, well resolved from analyte peak, proving the stability-indicating power of the method.The proposed method was found to be suitable for quantitative determination and the stability studies of risperidone in tablets.